The rough guide to England 2026 - Reeves, Joanna (Travel writer); Longley, Norm (Rough Guides, 2026)
Here is a practical travel guide to England with a free eBook featuring points-of-interest, structured lists of all sights and off-the-beaten-track treasures, with detailed maps, practical details about what to see and to do in England, how to get there and around, pre-departure information, as well as top time-saving tips.